Analisis Hukum terhadap Hak Pasien dalam Mengakses Layanan Kesehatan - Verawati, Verawati (Barongko: Jurnal Ilmu Kesehatan, 2025)
Patient rights are part of human rights guaranteed by the constitution and regulated in various laws and regulations in Indonesia. This study aims to analyze the legal framework governing patients' rights to access healthcare services, including legal protection, enforcement mechanisms, and barriers to implementation in the field. The research method used is normative legal research with a statute approach and qualitative analysis of secondary data in the form of regulations, legal literature, and previous research findings. The results indicate that patient rights are guaranteed in Law Number 36 of 2009 concerning Health, Law Number 44 of 2009 concerning Hospitals, and Minister of Health Regulation Number 4 of 2018 concerning Hospital Obligations and Patient Rights. However, obstacles persist, such as limited access in remote areas, lack of public understanding, and suboptimal complaint mechanisms and sanctions for violators. In conclusion, strengthening regulations, oversight, and public education are necessary to ensure effective fulfillment of patient rights.